Power Quality Improvement by Using Phase Shifting Transformer (International Journal of Innovative Research in Engineering & Management, 2022)
Non-linear loads like direct current  loads and induction motor drives are a major source of  harmonics in the power system. Multipulse converters are widely used to overcome the problem of harmonics.  This thesis highlights the performance comparison of  different multipulse converters which are simulated in  MATLAB/SIMULINK. Performance comparison of the  6-pulse, 12-pulse, 24-pulse and 48-pulse converters  feeding RL-load is performed. The phase shift in the  converters is achieved by using ziz-zag phase shifting  transformers. The Total Harmonic Distortion (THD) in  input current and input voltage along with ripple content  in the output voltage and output current are measured  and their corresponding waveforms are observed. Also,  performance comparison of 6-pulse, 12-pulse, 24-pulse  and 48-pulse converters is performed. The results  obtained with a multipulse converter are compared with  those obtained with the six pulse converter. It is  observed that multipulse converters provide better  results in terms of THD in input voltage and input  current. It is found that as the pulse number of a  converter increases, THD in input voltage and input  current along with ripple content in the output voltage  and output current is decreased.
Keywords: Phase Shifting; Multipurpose Converters; Power Quality; Harmonic Mitigation; Line Current Distortion